Soil-site suitability evaluation for cardamom - A case study - Krishnan, C R Shivaprasad, V S Korikanthimath, A V Gaddi, K V Niranjan, D H Venkatesh, P (Journal of Spices and Aromatic Crops, 2001)
Nineteen soil profiles representing seven soil series with sixteen mapping units were collected, described and mapped at Indian Institute of Spices Research, Cardamom Research Centre, Appangala, Madikeri, Karnataka for evaluating their suitability for cardamom cultivation. Soil and site properties such as climate, depth, slope, elevation, shade, texture, drainage, etc were compared with suitability criteria and the soils were assessed for growing cardamom. It is indicated that the well distributed rainfall of 1500-2000 mm with well drained conditions, a soil depth of more than 80 cm and 900-1200 m elevation support good crop of cardamom. The critical limit of Available Water Capacity was found to be 100 cm. Of the total area of the research station, 42 per cent area is highly suitable for cardamom cultivation. About 53 per cent of the area is moderately suitable and about 4 per cent is marginally suitable.